The Beneficial Role of Probiotic Lactobacillus in Respiratory Diseases - Du, Tingfeng; Lei, Aihua; Zhang, Naiyu; Zhu, Cuiming (Frontiers in Immunology, 2022)
Respiratory diseases cause a high incidence and mortality worldwide. As a natural immunobiotic, Lactobacillus has excellent immunomodulatory ability. Administration of some Lactobacillus species can alleviate the symptoms of respiratory diseases such as respiratory tract infections, asthma, lung cancer and cystic fibrosis in animal studies and clinical trials. The beneficial effect of Lactobacillus on the respiratory tract is strain dependent. Moreover, the efficacy of Lactobacillus may be affected by many factors, such as bacteria dose, timing and host background. Here, we summarized the beneficial effect of administered Lactobacillus on common respiratory diseases with a focus on the mechanism and safety of Lactobacillus in regulating respiratory immunity.